Review Of Islamic Law On The Sale And Purchase Of Sacrificial Animal Skins Among The Community - Ulfah, Putri Rahmaida; Sairazi, Abdul Hafiz; Ruslan, Ruslan; Khairiyah, Khairiyah; Saputri, Dika Idha; Madinah, Nuril (Sharia Journal and Education Center Publishing, 2023)
ABSTRACT This study examines the Review of Islamic Law Regarding the Sale and Purchase of Sacrificial Animal Skins Among the Community. Sacrifice is the ritual of slaughtering livestock such as goats, sheep, cows and buffaloes. Sacrifice is carried out by Muslims who can afford it on Eid al-Adha. The purpose of this research is to find out how the practice of buying and selling qurban animal skins is in the community? To find out how the review of Islamic law regarding the sale and purchase of sacrificial animals among the community? This study used a descriptive qualitative research method and the collection technique was carried out by collecting data by observing and interviewing the parties who were used as research informants. The interview technique that was carried out was by asking questions, one of which was via the media via WhatsApp to people I knew who I often saw or witnessed the buying and selling process of the sacrificial animals. The results of the research I got showed that usually people do this because they need to buy plastic to wrap, buy food and even drink for the slaughterers and even the money can also be used for their own personal interests. In Islamic law, it is forbidden to sell parts of the qurban animal in the form of meat, head, legs, bones and skin. Therefore, the law is clear that based on the Qur'an, hadith and the opinions of the scholars, it is argued that the sale and purchase of the skins of sacrificial animals is prohibited. Keywords: buy and sell, sacrificial animal skins ABSTRAK Penelitian ini mengkaji mengenai Tinjauan Hukum Islam Mengenai Jual Beli Kulit Hewan Qurban Di Kalangan Masyarkat. Kurban adalah ibadah penyembelihan hewan ternak seperti kambing,domba,sapi,dan kerbau. Berkurban dilakukan oleh umat muslim yang mampu pada Idul Adha.Tujuan penelitian ini adalah untuk mengetahui bagaimana praktik jual beli kulit hewan qurban ini di kalangan masyarakat? Untuk mengetahui bagaimana tinjauan hukum Islam mengenai jual beli hewan qurban di kalangan masyarakat?Penelitian ini menggunakan metode penelitian kualitatif bersifat deskriptif dan teknik pengumpulan nya dilakukan dengan mengumpulkan data dilakukan dengan observasi dan wawancara dari para pihak yang dijadikan informan penelitian. Teknik wawancara yang dilakukan adalah dengan bertanya tanya salah satunya dengan media via whatsapp kepada orang yang saya kenal yang saya ketahui sering melihat atau menyaksikan proses jual beli hewan qurban tersebut. Hasil penelitian yang saya dapatkan menunjukkan bahwa biasanya orang melakukan hal tersebut karena kebutuhan ingin membeli plastik untuk membungkus,membeli makanan bahkan minuman untuk para penyembelih nya bahkan uangnya bisa juga digunakan untuk kepentingan pribadi masing masing. Di dalam Hukum Islam Jual Beli kulit hewan qurban hukumnya adalah haram menjual sebagian dari hewan qurban baik berupa daging,kepala,kaki,tulang,dan kulit. Oleh sebab itu,jelas hukumnya bahwa berdasarkan al-qur’-an,hadis dan pendapat para ulama berpendapat bahwa jual beli kulit hewan qurban dilarang. Kata Kunci : Jual Beli, Kulit Hewan Qurban